2008
DOI: 10.1038/oby.2007.103
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Young Adulthood Is Related to Social Mobility Among Swedish Men

Abstract: Objective: Several studies have shown an inverse relationship between obesity and social status. The aim of this longitudinal study was to disentangle the relationship between BMI and social mobility between generations. Methods and Procedures: The study population consisted of 752,081 men, born between 1951 and 1965, who were Swedish citizens at conscription examinations. Intellectual capacity and BMI (kg/m 2 ) were measured at age 18 years. Childhood socioeconomic index (SEI) was measured at an approximate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…These findings are in agreement with Swedish data, which also show that obese men are often downwardly mobile (Karnehed et al, 2008). These findings are in agreement with Swedish data, which also show that obese men are often downwardly mobile (Karnehed et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with Swedish data, which also show that obese men are often downwardly mobile (Karnehed et al, 2008). These findings are in agreement with Swedish data, which also show that obese men are often downwardly mobile (Karnehed et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…The process is repeated annually and provides valuable anthropometric data on young men of a directive age [ 45 ]. Though these conscription systems are not outlined for collection of such data per se, they have successfully served as a basis for epidemiological studies in Switzerland [ 29 , 46 , 47 ], Sweden [ 48 , 49 ], Austria [ 50 52 ], and Germany [ 53 ]. Though limited to young males, the prevalence of conscripts’ OBOW remains a valuable research source because obesity in young adulthood increases the likelihood of being obese later in life, and the morbidity and mortality risks of men increase with advancing age [ 6 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further complicating this relationship is the concept of social mobility, in which people can move up or down the social hierarchy throughout the life-course. Previous research has shown the direction of mobility to be accompanied by improvement or worsening of health, and likewise changes in health can often be related to fluctuations in social circumstances [13,14]. Therefore, more information is needed on whether the association between early social disadvantage and later obesity can be modified by the process of social mobility during the life-course [13].…”
Section: Introductionmentioning
confidence: 99%